2006
DOI: 10.1007/s00125-006-0303-7
|View full text |Cite
|
Sign up to set email alerts
|

The release of the adipocytokine visfatin is regulated by glucose and insulin

Abstract: Aims/hypothesis The novel insulin-mimetic adipocytokine visfatin has been linked to the metabolic syndrome, but its regulation has not been characterised to date. Since insulinmimetic actions of visfatin may be part of the feedback regulation of glucose homeostasis, we hypothesised that visfatin concentrations are influenced by glucose or insulin blood levels in humans. Subjects, materials and methods In this randomised, doubleblind, placebo-controlled crossover study, nine healthy male subjects (age 26±6 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
190
5
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(218 citation statements)
references
References 24 publications
15
190
5
3
Order By: Relevance
“…Given that our subjects with GDM had a more pronounced rise in glucose after OGTT than both IG and control groups, this raises the possibility that higher visfatin levels in GDM could be related to the visfatin response to hyperglycaemia. Such a hypothesis is supported by the results of Haider et al [14], who demonstrated that glucose infusion (under clamp conditions) could increase visfatin concentrations. Recently, it has also been shown that subjects with established type 2 diabetes have significantly raised visfatin levels when compared with newly diagnosed type 2 diabetic subjects [15].…”
Section: Discussionmentioning
confidence: 68%
“…Given that our subjects with GDM had a more pronounced rise in glucose after OGTT than both IG and control groups, this raises the possibility that higher visfatin levels in GDM could be related to the visfatin response to hyperglycaemia. Such a hypothesis is supported by the results of Haider et al [14], who demonstrated that glucose infusion (under clamp conditions) could increase visfatin concentrations. Recently, it has also been shown that subjects with established type 2 diabetes have significantly raised visfatin levels when compared with newly diagnosed type 2 diabetic subjects [15].…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, Haider et al demonstrated both that visfatin released from adipocytes was enhanced by glucose in vitro and that hyperglycemia, during a glucose clamp, was associated with increased visfatin levels, which could be reversed by co-infusion of insulin (38). Haider et al also found, in pregnant women both with and without gestational diabetes (GDM), transiently increased visfatin levels after an oral glucose load (39).…”
Section: Visfatin Levels Increased After the Oral Glucose Loadmentioning
confidence: 99%
“…It is previously described as a pre-B cell colonyenhancing factor, which is abundantly expressed in visceral adipose tissue. Numerous evidences indicate that visfatin plays an important role in glucose homeostasis (5). It has been shown that visfatin binds to the insulin receptor at a distinct site, and exerts its hypoglycemic activity by reducing glucose release from hepatocytes, and stimulating glucose utilization in peripheral tissues (6).…”
Section: Introductionmentioning
confidence: 99%